Adult mental healthcare professionals’ experiences of family centred conversations with patients who are parents: a qualitative study - Dalton, Louise J.; de Cassan, Simone; Ilyas, Athif; Dunn, Abby; Rapa, Elizabeth (Frontiers in Psychiatry, 2024)
Many parents with a mental illness report a desire for both recognition of their parental role and support for themselves and their children. However, parents are often fearful of negative judgements from professionals about their ability to be a parent, which inhibits raising concerns about their children with clinical teams. Consequently, an essential first step to supporting families is for professionals to proactively identify which patients are parents, although evidence indicates this is not consistently part of services. Professionals could play a pivotal role in guiding parents about how to talk to their children about their mental illness; this in turn can facilitate family functioning and enable children to access evidence-based interventions. This approach is crucial for mitigating the welldocumented intergenerational risk of poorer outcomes and mental illness in children of affected parents. This study aimed to explore adult mental healthcare professionals' beliefs and experiences of talking with patients about: i) their role as parents ii) communication with their children about mental illness.Semi-structured qualitative interviews were conducted with 19 adult mental healthcare professionals with 4-30 years' experience of working with adult patients under the care of NHS adult mental healthcare services in England. Audio recordings were transcribed verbatim and analysed using an inductive coding approach following the principles of thematic analysis.All participants recognised their responsibility to identify patients' children through routine safeguarding protocols, but supporting patients around telling their children the diagnosis was less common. Many participants expressed concerns that raising the topic of children with patients could conflict with other parts of their professional role or would not be welcomed. Obstacles to these conversations were identified, across individual, environmental and organisational factors. Potential facilitators included specific staff training and resources for clinical teams and families around how to tell children about mental illness.Adult mental healthcare professionals would benefit from enhanced training on the importance and methods of guiding parents to communicate with their children about mental illness. This should include routine identification of which patients are parents and recognition of the impact of an adult's mental illness on the wider family system.